Adjacency Pairs in Drama Script â€œTeen Angelâ€ by D.M Larson - Ita Permatasari (Ahmad Dahlan Journal of English Studies, 2017)
Taking part as one of the important roles in globalization era, comprehending English should be done in order to conquer some aspects affected by it such as economy, social and politic. As the bridge of communication between two people, conversation becomes one of the parts of language that is analysed by language practitioner. In this research, the researcher did Conversation Analysis (CA) and use the the result of Conversation Analysis to be used as the materials in speaking and writing class. The data was taken from the drama script entitled â€œTeen Angelâ€ by D.M Larson. The two research questions; (1) What are the types of adjacency pairs formed in the conversations between characters involved in this drama? The result of the analysis shows that there are, 245 turns, 103 data (turn-taking) of adjacency pair classified into 13 types of adjacency pairs, and 5 pre-sequence and 2 insertion sequences occurred.Â